Operationalising Strong Sustainability: Definitions, Methodologies and Outcomes. (1st August 2004) - Özkaynak, Begüm; Devine, Pat; Rigby, Dan
While acknowledging the absence of a single definition or theory of sustainability, this paper argues that a discussion of sustainability which refers only to definitions is pointless without an understanding of how the definitions are operationalised. In this context, the paper considers the operationalisation of strong sustainability. The definitions and operationalisation of strong sustainability most closely associated with (i) neoclassical environmental economics and (ii) ecological economics are discussed and compared. This analysis raises questions about the extent to which ecological economics has been able to influence real-world decisions and policy. The paper ends by considering whether the economic and political power structure taken as given by ecological economics is compatible with its policy perspective.